Perubahan Karakteristik Arsitektur pada Rumah Tradisional: Studi Kasus Rumah Tuo di Tanjung Agung Kota Bengkulu - Iffah Karimah; Dyah Titisari Widyastuti (Arsir: Jurnal Arsitektur, 2025)
Rumah tuo is a traditional house of the Lembak Tribe in Tanjung Agung, Bengkulu City, which reflects local identity and values ​​through its architectural characteristics. Rumah tuo has undergone changes in several aspects. This study uses a qualitative method with data collection through observation, interviews, and documentation. Data analysis refers to three aspects: spatial systems, physical systems, and model systems. The results of the study show that there are various patterns of change in the tuo house. In the spatial aspect, there is an addition of a business area, an addition of a bedroom with a modified space, and a bathroom in the house. In the physical aspect, the house which originally used traditional materials such as wood and pelupuh has switched to using more modern materials such as concrete. In the stylistic aspect, although there is an addition of a new form to the facade, some houses still retain their original components. Overall, the additions that occur no longer refer to local elements and display new forms and materials. However, traditional elements such as old doors and windows are maintained, reflecting the community's efforts to maintain the original characteristics of rumah tuo Environmental factors, household and business activity needs, and the economy also influence change.